Rancang Bangun Sistem Monitoring Jaringan Pada Perusahaan Perhubungan - Ananda, M. Ricky; Marpaung, Noveri Lsybetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Developed technology charts required in various installments of computer-network technology. Computer network infrastructure is the most basic component that must be built properly. Network stability, among others, concerns network traffic, is the core that must always be maintained and its quality is maintained. The navigation district is a government agency under the ministry of transportation that utilizes network technology to support information needs. Riau Province District has a ship traffic service installation. Frequent bugs in marine traffic monitoring systems are the network connected to the Vassel Trafic Service (VTS) down due to bad weather, damage to the LAN port of the radio link. Leaving the system unable to communicate with ships sailing in VTS traffic. The dude application successfully logged in to the company to help.Keywords: LAN, Mikrotik, The dude